Diversity of Chironomidae (Diptera) breeding in the Great Stour, Kent: baseline results from the Westgate Parks non-biting midge project. Issue 11 (19th March 2021) - Vega, Rodrigo; Brooks, Stephen J.; Hockaday, Wendy; Lee, Scarlett; Vane-Wright, Richard I.
ABSTRACT: Chalk rivers and streams are of conservation importance due to their ecological diversity, historical relevance and economic value. With more than 200 chalk watercourses, England is considered unusual in having the most chalk rivers in the world. However, due to increasing anthropogenic activities, many English chalk rivers and streams are becoming badly degraded. The non-biting midges or chironomids (Diptera, Chironomidae) are considered key-stone taxa in aquatic food webs, and have been used as ecological indicators of freshwater quality and environmental stress. Here we determined the generic richness, diversity, and community structure of Chironomidae across six sites in the mid-section of the Great Stour in Kent, a chalk river for which concern has been expressed regarding both water and habitat quality. Based on the morphological identification of 1336 insect larvae from the six sites (four in Westgate Parks, Canterbury, and two at nearby locations upstream and downstream from Canterbury City), a total of 20 genera of Chironomidae were identified, including some taxa indicative of freshwater habitats with low levels of organic pollution. There were different levels of generic richness and diversity among sites, and while there was little variation in the community composition among the sites within Westgate Parks, there were noticeable generic differences among Westgate Parks sites compared with those upstream and downstream, showing the highest complementarity and Beta diversity values. Overall, the results were comparable with other studies on chironomids in chalk rivers and other river systems. Although spatially limited to a small stretch of river, this represents the first study on chironomids in the Great Stour and provides baseline information on the diversity and structure of this important insect group with aquatic larvae, useful for the objective interpretation of any future biological assessments and monitoring programmes on the Kentish Stour, and also for comparisons with other chalk rivers.